2014
DOI: 10.1108/ijrdm-10-2012-0094
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency measurement of Indian retailers using Data Envelopment Analysis

Abstract: Purpose – The purpose of this paper is to analyze the performance of Indian retailers in recent past and derive meaningful insight for practicing managers in this area. Design/methodology/approach – This paper analyses the economic efficiencies of select Indian retailers using three related methodologies: Data Envelopment Analysis (DEA), Malmquist Productivity Index (MPI) and Bootstrapped Tobit Regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
0
35
0
3
Order By: Relevance
“…Bonesronning and Rattso used Jackknifing in their analysis, they ran DEA 34 times and dropped off one DMU every time. 32 Mostafa used Jackknifing to test the stability of its study on the US specialty retailers and food consumer stores, but it's quite different from the research of Bonesronning and Rattso for he only dropped the efficient units that construct the frontier. In our research, we adopt the method of Mostafa.…”
Section: Sensitivity Testmentioning
confidence: 99%
“…Bonesronning and Rattso used Jackknifing in their analysis, they ran DEA 34 times and dropped off one DMU every time. 32 Mostafa used Jackknifing to test the stability of its study on the US specialty retailers and food consumer stores, but it's quite different from the research of Bonesronning and Rattso for he only dropped the efficient units that construct the frontier. In our research, we adopt the method of Mostafa.…”
Section: Sensitivity Testmentioning
confidence: 99%
“…The results revealed that shop age has a positive significant influence on bookshop efficiency, whereas manager experience, staff experience, and the education level of the shop manager do not. Gandhi and Shankar [15] studied the determinants of efficiency in 18 Indian retailers. The results showed that the number of retail outlets and M&A can be considered the driving forces influencing efficiency.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Sales revenue was used as an output variable in all previous studies [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] and is one of the most important KPIs in most companies. In this study, the daily average sales revenue was used.…”
Section: Input/output Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…21 đã phân tích 24 cửa hàng của chuỗi nhà hàng 211 thức ăn nhanh ở Hoa Kỳ. Ganhi và Shankar (2014)22 212 đã đánh giá hiệu quả của 11 nhà bán lẻ tại Ấn Độ.213 Ko và cộng sự (2017)23 đã phân tích hiệu quả 32 cửa 214 hàng bán lẻ tại Hàn Quốc.Bảng 1 trình bày tóm tắt các 215 nghiên cứu sử dụng DEA với việc việc xem xét các yếu 216 tố đầu vào và đầu ra khác nhau để đo lường và phân 217 tích hiệu quả hoạt động của các đơn vị ra quyết định 218 (DMU -decision making unit). Phương pháp DEA cung cấp một điểm số cho mỗi 220 đơn vị ra quyết định nhưng nó không xác định các 221 yếu tố ảnh hưởng đến hiệu quả.…”
unclassified